Psychological empowerment as moderator of the relationship between core self-evaluation and proactive work behaviour - Chiyem Lucky Nwanzu; Sunday Samson Babalola (Cogent Business & Management, 2024)
AbstractThis study examined the relationships between core self-evaluation, psychological empowerment, and proactive work behaviour. Oriented by situation strength theory, the study also examined the moderation role of psychological empowerment in core self-evaluation and proactive work behaviour relationships. This study relates personal characteristics of core self-evaluation, the situational variable of psychological empowerment, to organisationally desirable employee outcomes of proactive work behaviour. While core self-evaluation and psychological empowerment were analysed as one-dimensional variables, proactive work behaviour has four dimensions: problem prevention behaviour, individual innovation behaviour, voice behaviour, and taking charge behaviour. Two hundred and fifty-five employees sampled from public and private organisations were used for data analysis. Data were analysed with the PROCESS tool hosted in SPSS regression. The results showed that psychological empowerment was positively associated with proactive work behaviour and moderated the relationship between core self-evaluation and proactive work behaviour. The study contributes to the body of knowledge with the potential for a middle-range theory on psychological empowerment and proactive work behaviour relationship, substantially supports situation strength theory, and provides knowledge on the best combination of core self-evaluation and psychological empowerment for proactive work behaviour.